Interplay Between Brain Dominance, Reading, and Speaking Skills in English Classrooms - Li, Shanshan; Hanafiah, Waode; Rezai, Afsheen; Kumar, Tribhuwan (Frontiers in Psychology, 2022)
One of the popular theories in psychology that potentially contributes to the development of teaching and learning programs is brain dominance. According to this theory, the brain is categorized into two hemispheres based on personal traits and cognitive styles. It is interesting to investigate the correlation between brain dominance and second language learning. Therefore, this study set out to examine the correlation between brain dominance and the development of English reading, and speaking skills. For this purpose, the required data were randomly gathered from 230 sophomore students in four different universities and were analyzed through a Pearson Chi-Square test, a Kruskal–Wallis test, and a Mann–Whitney test. Findings evidenced a significant correlation between brain dominance and reading skills. Three categories of brain dominance groups differ in reading skills in which moderate right-brain shows the highest score. Concerning the speaking skills, however, the results documented no significant correlation between brain dominance and speaking skills. Three groups of brain dominance were not significantly different in three aspects of speaking skills, including accuracy, fluency, and comprehensibility. The study concludes by proposing a range of implications and some avenues for further research.